Whole-Genome Sequencing of Endangered Dengchuan Cattle Reveals Its Genomic Diversity and Selection Signatures - Jin, Liangliang; Qu, Kaixing; Hanif, Quratulain; Zhang, Jicai; Liu, Jianyong; Chen, Ningbo; Suolang, Quji; Lei, Chuzhao; Huang, Bizhi (Frontiers in Genetics, 2022)
Dengchuan cattle, the only dairy yellow cattle and endangered cattle among Yunnan native cattle breeds. However, its genetic background remains unclear. Here, we performed whole-genome sequencing of ten Dengchuan cattle. Integrating of our data with the publicly-available data, Dengchuan cattle was observed to be highly interbred than other cattle in the dataset. Furthermore, the positive selective signals were mainly manifested in candidate genes and pathways related to milk production, disease resistance, growth and development, and heat tolerance. Notably, five genes (KRT39, PGR, KRT40, ESR2 and PRKACB) were significantly enriched in estrogen signaling pathway. Moreover, the missense mutation in PGR gene (c.190T > C, p.Ser64Pro) showed a homozygous mutation pattern with higher frequency (83.3%) in Dengchuan cattle. In addition, a large number of strong candidate regions matched genes and QTLs related to milk yield and composition. Our research provides a theoretical basis for analyzing the genetic mechanism underlying Dengchuan cattle with excellent lactation and adaptability, crude feed tolerance, good immune performance and small body size, and also laid a foundation for genetic breeding work of Dengchuan cattle in future.